FERONIA and Her Pals: Functions and Mechanisms - Chao Li; Hen‐Ming Wu; Alice Y. Cheung (2016)
Current research into the FERONIA family of receptor kinases highlights both questions and opportunities for understanding signaling strategies in plant growth and survival.